CLINICAL SUPERVISION GUIDELINE PATTERNED ON REFLECTIVE PEDAGOGICAL PARADIGM TO ENHANCE TEACHER’S COMPETENCY IN STRADA JAKARTA - Aurelia Maria Djanu Rombang; Hotmaulina Sihotang (JURNAL HANDAYANI PGSD FIP UNIMED, 2020)
Abstract: Clinical supervision guideline patterned on reflective pedagogical paradigm to enhance teacher’s competency in Strada Jakarta. This study aims to identify things that are still lacking in supervision guidance products used in Strada schools. The results of the study indicate that there are some shortcomings that must be updated from the manual which so far has been used. There’c product produced in the form of a book titled Guidelines for clinical supervision that is patterned on the reflective pedagogical paradigm which is a theory of clinical supervision and learning patterns of reflective pedagogical paradigm, a technical guideline for supervision.Keywords: Clinical supervision. Reflective pedagogical paradigm, Teachers’ competency.Abstrak: Panduan pengawasan klinis yang terpadu pada paradigma pedagogi reflektif untuk meningkatkan kompetensi guru di Strada Jakarta. Penelitian ini bertujuan untuk mengidentifikasi hal-hal yang masih kurang dalam produk bimbingan pengawasan yang digunakan di sekolah Strada. Hasil penelitian menunjukkan bahwa ada beberapa kekurangan yang harus diperbarui dari buku pedoman yang sejauh ini telah digunakan. Ada produk yang dihasilkan dalam bentuk buku berjudul Pedoman untuk pengawasan klinis yang berpola padaparadigma pedagogis reflektif yang merupakan teori pengawasan klinis dan pola pembelajaran paradigma pedagogis reflektif, pedoman teknis untuk pengawasan. Kata kunci: Supervisi klinik, Paradigma pedagogik Reflektif, Kompetensi guru